Household solid waste sampling for Mar del Plata City, Argentina - Menna, Máximo (2001)
This work arices from and adrement between Universidad National de Mar del Plata (UNMDP) and the Municipality of Partido de General Pueyrredon, Buenos Aires, Province, ARgentina. A sampling was designed taking, as the starting point, data from a population and housing census (INDEC, 1991) for the evaluation of home solid waste in Mar del Plata city. The sample type in study concient of stratification with replacement, according to social - economic - cultural variables. Waste was classified in origen in six fraction: paper/cardboard, glass, organic, plastic, metal and other. Waste weightings were obtaining dayling, according to housing, stratun and fraction components. Data obtained during the for seasons in 1997 are shown in the present work, from wich de percentajes of ich waste type and the results of statistical calculations for the organic fraction and for the total of the housing solid waste were obtained.